2022
DOI: 10.1039/d1nj04792b
|View full text |Cite
|
Sign up to set email alerts
|

Ni(OH)2 Coated CoMn-layered double hydroxide nanowires as efficient water oxidation electrocatalysts

Abstract: Core-shell nanowires of first-row transition metals are important members of nanostructured electrocatalysts for water oxidation owing to their superior electrocatalytic performance and tremendous promise as substitutes for noble-metal-based electrocatalysts. Recently,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…To investigate the origin of outstanding OER performance and crystallinity effect due to calcination, XRD analysis was carried out at different calcination temperatures (Figure S5c). XRD images revealed that before annealing, the original sample exhibited a typical LDH structure (JCPDS no. 10-0144).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the origin of outstanding OER performance and crystallinity effect due to calcination, XRD analysis was carried out at different calcination temperatures (Figure S5c). XRD images revealed that before annealing, the original sample exhibited a typical LDH structure (JCPDS no. 10-0144).…”
Section: Resultsmentioning
confidence: 99%
“…Then, dry nitrogen was used for drying the NFs. Based on our previous study, 10 the Co/ Mn molar ratio of 4:1 was further employed to synthesize precursors. A homogeneous precursor solution was then prepared by dissolving 2 mmol Co(NO 3 ) 2 •6H 2 O (0.5821 g), 0.5 mmol MnSO 4 •H 2 O (0.0845 g), 0−2 mmol FeCl 3 •6H 2 O (0−0.5406 g), 6 mmol CH 4 N 2 O (0.3604 g), and 5 mmol NH 4 F (0.1850 g) in 40 mL of ultrapure water.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Nickel nanoparticles and their oxides have emerged as efficient catalysts in hydrogenolysis, 40,41 dehydrogenation, 42 condensation reactions, 43,44 reduction reactions, 45 and C-C bond formation. [46][47][48] A perusal of the literature reveals that Ni(OH) 2 NPs have been used in the field of electrocatalysis, [49][50][51][52][53] photocatalysis, [54][55][56][57] supercapacitors, [58][59][60][61] and heterogeneous catalysis, [62][63][64] yet Ni(OH) 2 NPs remain relatively less explored in the arena of catalysis. Unsupported Ni(OH) 2 NPs exhibit a tendency to agglomerate.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, 3D r-FeOOH/α-Ni(OH) 2 /NF with binary hybridized heterostructure was synthesized by fast room temperature reduction, and a small potential of 1.66 V was required for a large current density of 1.5 A cm −2 in base media. Li et al 24 synthesized Ni(OH) 2 @CoMn-LDH core-shell nanowires on nickel foam (NF) by hydrothermal process and followed by electrodeposition, which remained stable over 25 h.…”
mentioning
confidence: 99%